2017
DOI: 10.32890/mjli2017.14.1.4
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study of the Effects of the Neurocognitive-Based Model and the Conventional Model on Learner Attention, Working Memory and Mood

Abstract: Purpose-The attention, working memory, and mood of learners are the most important abilities in the learning process. This study was concerned with the comparison of contextualized attention, working memory, and mood through a neurocognitive-based model (5P) and a conventional model (5E). It sought to examine the significant change in attention, working memory, and mood of Grade 9 students after the intervention of a neurocognitive-based model (5P) and a conventional model (5E) in an experimental group and a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 16 publications
0
6
0
1
Order By: Relevance
“…Students with dyscalculia have limitations in their working memory, resulting in poor arithmetic skills. This is supported by Srikoon et al (2017), who argue that working memory is one of the most significant abilities in the learning process. In addition to difficulty in counting and mathematical computation, students with dyscalculia also experience difficulties in time management (Aquil & Ariffin, 2020a).…”
Section: Discussionmentioning
confidence: 78%
“…Students with dyscalculia have limitations in their working memory, resulting in poor arithmetic skills. This is supported by Srikoon et al (2017), who argue that working memory is one of the most significant abilities in the learning process. In addition to difficulty in counting and mathematical computation, students with dyscalculia also experience difficulties in time management (Aquil & Ariffin, 2020a).…”
Section: Discussionmentioning
confidence: 78%
“…This allows students to gain a better knowledge of scientists and improve their perceptions and attitudes of scientists. Further research from Malaysia by Srikoon, Bunterm, Nethanomsak, and Ngang (2017), indicated that a neurocognitivebased model (5P) of learning management affected students' interests more than the conventional contextualized model (5E) of learning management. Anderson (2009) also suggested that there be a synthesis of neurocognitive learning theory and the constructivist philosophy of science teaching and learning to improve the attention of learners.…”
Section: Discussionmentioning
confidence: 99%
“…Anderson (2009) also suggested that there be a synthesis of neurocognitive learning theory and the constructivist philosophy of science teaching and learning to improve the attention of learners. The latter has already become a major guiding model for instructional design in many disciplines (Srikoon et al, 2017). Also, socio-scientific issues (SSIs) are used to improve scientific literacy related to students' rationality, analytical decisions, and synthesis and evaluation of data (Çalik et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Pendapat lain mengatakan bahwa kemampuan berpikir kreatif timbul dari potensi hingga memunculkan aksi kreatif untuk memproduksi hal baru dan unik dengan memanfaatkan hal yang tersedia (Arini, 2017). Berpikir kreatif secara umum dilihat sebagai proses pendataan untuk menghasilkan wawasan, ide atau konsep baru (Srikoon et al, 2017). Kemampuan berpikir kreatif adalah serangkaian aktivitas kognitif individu yang digunakan sebagai respons terhadap objek, masalah, atau keadaan tertentu, atau suatu bentuk upaya terhadap peristiwa dan masalah tertentu yang bergantung pada kapasitas individu (Birgili, 2015).…”
Section: Pendahuluanunclassified